Pendampingan Perencanaan Desa Wisata Pantai Berbasis Masyarakat dalam Upaya Peningkatan Ekonomi Gampong - Caisarina, Irin; Zuraidi, Evalina; Meria Burhan, Issana (Pencerah, 2023)
The development of tourist villages requires the participation of local communities in all stages of development starting from planning, implementation and supervision. However, in reality, the community is often not involved, their participation is even neglected. The area along the coast in Lhok Nga District, Aceh Besar Regency, Indonesia, especially in Gampong Mon Ikeun, has enormous potential to be developed as a beach tourism village. Even though the local government has made efforts to develop the area in this village, the reality is that tourism activities in the village have not been able to bring prosperity to the community. This community service activity (PKM) by a team from Universitas Syiah Kuala aims to provide assistance in the planning process for coastal tourism areas in the village. The approach taken is to involve community participation in identifying the potential and problems that exist in their area in an effort to develop their village as a coastal tourism area that can support the local community's economy. The product produced is in the form of a development plan document for the coastal tourism area which can later be used as a guideline in implementing the tourism development of Gampong Mon Ikeun in the future and enhance their prosperity.